2
$\begingroup$

I'm given the equation $F=(a+b+c)(a'+b')(a+b'+c)$ and it's supposed to simplify into a sum of two product terms, each with two literals. I know the answer is $ab'+a'c$, but I'm unsure how to get there. I know the laws and postulates that I need to use. As much as I hate to admit it, I only know how to handle sums of products.

$\endgroup$
1
$\begingroup$

$$(a+b+c)(a'+b')(a+b'+c) = [aa'+ab'+a'b+bb'+a'c+b'c](a+b'+c) \\ = [0+ab'+a'b +0+a'c+b'c](a+b'+c) \\ = (ab'+a'b+a'c+b'c)(a+b'+c) \\ = aab' + ab'b'+ab'c + a'ab+a'bb'+a'bc +a'ac+a'b'c+a'cc+ab'c+b'b'c+b'cc \\= ab'+ab'+ab'c+0+0+a'bc+0+a'b'c+a'c+ab'c+b'c+b'c \\ = (ab'+ab') + ab'c+a'c(b+b')+a'c+b'c(a+1+1) \\ = ab'+ab'c+a'c(1)+a'c+b'c \\ = ab'(1+c) + a'c+b'c \\ = ab'+a'c+b'c$$

I've tried to simplify this in a few different ways but I always come out with the same answer which involves 3 terms. I suppose you could simplify the last line into $ab'+c(ab)'$ using DeMorgan's rule but I don't see how you obtain only $ab'+a'c$ in the end. I am fairly certain an error in my expansion/simplification will become noticeable if someone else would be kind enough to check it.

$\endgroup$
0
$\begingroup$

$$ F = (a + b + c) ( \bar a + \bar{b}) (a + \bar{b} + c) $$ I would rearrange this to put the outer two terms together $$= (a + b + c) (a + \bar{b} + c)( \bar a + \bar{b}) $$ since you can distribute with those two and cancel out a lot of things $$ = (a + a \bar{b} + ac + c) ( \bar a + \bar{b}) $$ For example $aa$ became $a$ and things like $a \bar{a}$ are just dropped since you can't have both $a$ and $\bar{a}$ at the same time. Then if you distribute the right hand term into the left you get $$ = \bar{a} c + a \bar{b} c + \bar{b} c $$ where again we had many terms with $a \bar{a}$ or $b \bar{b}$ that we can just drop. For the very last step you can simplify the last two terms :)

$\endgroup$
0
$\begingroup$

$$(a +b+c)(a'+b')(a +b'+c)= \text{ (Adjacency)}$$

$$(a+c)(a'+b')= \text{ (Distribution)}$$

$$aa'+ab'+ca'+cb'=\text{ (Complement)}$$

$$0+ab'+ca'+cb'=\text{ (Identity)}$$

$$ab'+ca'+cb'=\text{ (Consensus)}$$

$$ab'+ca'= \text{ (Commutation)}$$

$$ab'+a'c$$

The Consensus Law says that:

Consensus

$XY +Y'Z=XY +Y'Z +XZ$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.